Design of a novel epitope-based tetravalent subunit vaccine against dengue virus: An immunoinformatic approach - Tanbin Jahan Ferdousy; Md Mehedy Hasan Miraz; Tawsif Al Arian; Md Afif Ullah; Md Tahsinul Haque Risat; Most. Afrin Akter; Shouhardyo Kundu; Bidduth Kumar Sarkar; Arghya Prosun Sarkar; Abul Bashar Ripon Khalipha; Sukalyan Kumar Kundu (PLoS ONE, 2026)
Dengue imposes a profound global impact, with millions affected annually. Its transmission by Aedes mosquitoes poses significant challenges to combat, aggravated by urbanization and climate change. Despite efforts, no impeccable antiviral treatment exists to date, highlighting the urgency for a vaccine. Developing one encounters hurdles like the four distinctive serotypes of the virus and complex immune responses. In this study, we employed an immunoinformatics approach to design an epitope-based tetravalent subunit vaccine aimed at confronting all DENV serotypes. The study contemplates epitope prediction and screening, physicochemical assessment, molecular docking, molecular dynamics (MD) simulations, immune simulations, and in silico cloning. The vaccine construct comprises human β-defensin 3 adjuvant and 23 epitopes joined with linkers. Notably, the vaccine has an antigenicity of 0.9319 with 97.35% population coverage worldwide. Molecular docking with toll-like receptor 2 (TLR2) and TLR4 showed promising interactions with lowest energies of −1240.5 kJ/mol (76 members) and −1393.3 kJ/mol (40 members), respectively, exhibiting significant electrostatic, van dar Waals, and other interactions. Molecular dynamics (MD) simulations of 200 nanoseconds revealed the vaccine to be stable and flexible with the receptors. The solvent accessibility and radius of gyration were also in suitable ranges. The three-dose vaccine regimen elicited a robust and durable multi-lineage immune response, characterized by stable B and T-cell memory, sustained surveillance, and high-titer antibody production (IgM/IgG) alongside a pro-inflammatory cytokine profile (IFN-γ and IL-2) for effective antigen clearance. These findings suggest that our vaccine outperforms any other Dengue vaccine developed to date. However, since this study was conducted through in silico methods, in vitro and in vivo validations are required to confirm the vaccine as a potential candidate for clinical trials.